Pengaruh Konsentrasi Pupuk Mikro dan Magnesium Phospat terhadap Pertumbuhan dan Produksi Kacang Tanah (Arachis hypogeae L.) - Hidayatulloh, Achmad Nurid; Wahyuni, Endang Sri (JURNAL AGROPLANT, 2022)
One of the effort to improve peanut production can be done with fertilization. Effect of fertilizer to the land is to create a high level of nutrients and can improve the quality of crops. Fertilization through leaves meant that the nutrients can be absorbed quickly by plants. macro elements such as magnesium (mg) and micronutrients such as phosphate (P) and micro nutrients that plants need more peanuts. The purpose of this study was to determine the effect of Micro and Magnesium Phosphate fertilizer on the growth and production of groundnut (Arachis hypogeae L.). This research was conducted in paddy fields in August up to November 2016, in the village Kertonegoro, district Jenggawah Jember district. The study was conducted using a randomized block design (RAK) consisted of two factors with three replications. The first factor is the concentration of fertilizer Micro (M) consisting of 0 g/l (M0), 0.125 g/l (M1), 0.25 g/l (M2) and the second factor is the concentration of Magnesium Phosphate fertilizer 0 ml/l ( MgP0); MgP1 {2 ml/l (in preparation for planting, flower formation, fruit and ripening fruit), 0.5 ml/l at 15 HST and 1 ml/l each 1 week)} and MgP2 (Magnesium Phosphate Concentrations 2x standard). The results showed that the fertilizer Micro with a concentration of 0.25 g/l (M2) influence as much as 22.13 nyataterhadap number of pods and pod weight of 43.78 grams. Magnesium Phosphate Fertilizer with standard concentration (MgP1) significantly affect the number of branches as much as 5.38, while the Magnesium Phosphate fertilizers with standard 2x concentration (MgP2) significantly affect stover weight of 22.89 grams. The combination of Micro and Magnesium Phosphate fertilizers (M2MgP1) get the highest number of leaves at age 21 HST as many as 9.13.